Exploring the Vision of an Equitable Prostate Cancer Care Delivery System: Perspectives of Black Men in Charleston, South Carolina - Sherrie Flynt Wallington; Kris Bennett; Marvella E. Ford; Lee Moultrie; Melanie Slan; Reginald D. Tucker-Seeley (American Journal of Men's Health)
Prostate cancer presents a pressing public health challenge in the United States and disproportionately affects Black men. Despite efforts to address these disparities, equitable access to timely diagnosis and optimal treatment remains elusive for many Black men. Using focus group discussions, the researchers aimed to understand what constitutes equitable cancer care and identify tools needed by Black men for equitable navigation of prostate cancer care. Through a community-engaged qualitative design, 29 Black males aged 40 to 75 participated in virtual and in-person focus groups in August 2023. Data analysis employed NVivo qualitative software and an inductive thematic approach. Three overarching themes emerged: general prostate knowledge, barriers and experiences, and preferred communication channels. Participants discussed their understanding of prostate cancer, barriers to screening, experiences with healthcare delivery, and trusted information sources. Findings revealed nuanced differences between groups but emphasized the importance of clear communication, respect, and community support in cancer care. The researchers’ future recommendations include developing educational programs, addressing systemic barriers, providing early education on prostate cancer risk, implementing training for providers, creating support groups, and revisiting national guidelines for Black men. The study provides valuable insights into the experiences and needs of Black men when accessing equitable prostate cancer care that are essential for addressing disparities in cancer outcomes.